1996
DOI: 10.1093/nar/24.8.1508
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide N3'-->P5' phosphoramidates as antisense agents

Abstract: Uniformly modified oligonucleotide N3'-->P5' phosphoramidates, where every 3'-oxygen is replaced by a 3'-amino group, were synthesized. These compounds have very high affinity to single-stranded RNAs and thus have potential utility as antisense agents. As was shown in this study, the oligonucleotide phosphoramidates are resistant to digestion with snake venom phosphodiesterase, to nuclease activity in a HeLa cell nuclear extract, or to nuclease activity in 50% human plasma, where no significant hydrolysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 32 publications
2
50
0
Order By: Relevance
“…1) in d(AnTnGnAnCn)rU are resistant to chemical and nuclease degradation, a requirement for an effective therapeutic (20,(34)(35)(36). The results show that the oxygen to amino and 2Ј OH to 2Ј H functional group modifications (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…1) in d(AnTnGnAnCn)rU are resistant to chemical and nuclease degradation, a requirement for an effective therapeutic (20,(34)(35)(36). The results show that the oxygen to amino and 2Ј OH to 2Ј H functional group modifications (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…These results are consistent with (i) the increase in triplex stability of np oligonucleotides as previously described, and (ii) the resistance toward nucleases observed with np oligonucleotides under our experimental conditions (data not shown; ref. 38). Also, nuclear proteins have been shown to bind non-sequencespecifically to po oligonucleotides (36).…”
Section: Resultsmentioning
confidence: 99%
“…Also, nuclear proteins have been shown to bind non-sequencespecifically to po oligonucleotides (36). Preliminary experiments have shown that cellular proteins bind np oligomers less efficiently than po oligonucleotides (38). This may lead to the better availability of np than of po oligomers.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of oligos is still hindered by several critical problems, including an instability to nuclease, sequence nonspecificity, and inadequate cellular uptake (10,11). A variety of chemically modified oligos, including phosphorothioate and methylphosphonate oligos, have been developed as a measure to augment stability against nucleases.…”
Section: Introductionmentioning
confidence: 99%